Modernity and the Denominational Imperative: The Children’s Aid Society of Halifax, 1905-1925 - Lafferty, Renée (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 2002)
AbstractThis study of the Children's Aid Society in Halifax offers a challenge to traditional narratives which see the agency as a harbinger of de-institutionalisation and professionalisation in early twentieth-century Canada. In Halifax, the Society was not part of an imposed and deliberate programme of modernisation, but was seen as a means to reinforce the existing system during a period of social and economic upheaval. Its foundation was integrally linked to the peculiarities of the city's circumstances, to fears about threats to childhood ideals, and to the operation of the denominational imperatives of existing institutions. Indeed, there was continued strong support for denominational, institutional care in the city, fostered in large part by shared ideas between institutional and governmental child care workers about the priorities and philosophies of their child-welfare system.